The Role of the Islamic Youth in Mobilizing Non-Formal Schools for Social Empowerment - Choir, Ifil; Aziz, Husein (International Journal of Islamic Thought and Humanities, 2024)
This article discusses the strategic role of the younger generation in initiating and managing non-formal schools as a tangible form of social empowerment in the midst of limited access to formal education. Through a descriptive qualitative approach, this study reveals various alternative education initiatives driven by young people in urban and rural areas, such as Yogyakarta, Surabaya, and East Flores. This non-formal school is not only a learning space, but also a vehicle for character building, strengthening community values, and resistance to structural injustice. The findings show that the involvement of young people in non-formal education is driven by a spirit of solidarity, social sensitivity, and local innovation based on community assets. However, the movement still faces challenges in terms of sustainability, legality, and policy support. Therefore, synergy is needed between the state, society, and the private sector to recognize and support the work of the young generation in alternative education as part of sustainable social development.